Session Topic: Financial Constraints and Minority Economic Development: Discussion - Lindsay, Robert (Journal of Finance, 1971)
Robert Lindsay, Session Topic: Financial Constraints and Minority Economic Development: Discussion, The Journal of Finance, Vol. 26, No. 2, Papers and Proceedings of the Twenty-Ninth Annual Meeting of the American Finance Association Detroit, Michigan December 28-30, 1970 (May, 1971), pp. 466-468